Integrated functional genomic analysis identifies regulatory variants underlying a major QTL for disease resistance in European sea bass - Robert Mukiibi; Serena Ferraresso; Rafaella Franch; Luca Peruzza; Giulia Dalla Rovere; Massimiliano Babbucci; Daniela Bertotto; Anna Toffan; Francesco Pascoli; Sara Faggion; Carolina Peñaloza; Costas S. Tsigenopoulos; et al. (BMC Biology)
Abstract Background Viral nervous necrosis (VNN) is an important viral disease threatening global aquaculture sustainability and affecting over 50 farmed and ecologically important fish species. A major QTL for resistance to VNN has been previously detected in European sea bass, but the underlying causal gene(s) and mutation(s) remain unknown. To identify the mechanisms and genetic factors underpinning resistance to VNN in European sea bass, we employed integrative analyses of multiple functional genomics assays in European sea bass. Results The estimated heritability of VNN resistance was high (h 2 ~ 0.40), and a major QTL explaining up to 38% of the genetic variance of the trait was confirmed on chromosome 3, with individuals with the resistant QTL genotype showing a 90% survivability against a VNN outbreak. Whole-genome resequencing analyses narrowed the location of this QTL to a small region containing 4 copies of interferon alpha inducible protein 27-like 2A (IFI27L2A) genes, and one copy of the interferon alpha inducible protein 27-like 2 (IFI27L2) gene. RNA sequencing revealed a clear association between the QTL genotype and the expression of two of the IFI27L2A genes, and the IFI27L2 gene. Integration with chromatin accessibility and histone modification data pinpointed two SNPs in active regulatory regions of two of these genes (IFI27L2A and IFI27L2), and transcription factor binding site gains for the resistant alleles were predicted. These alleles, particularly the SNP variant CHR3:10,077,301, exhibited higher frequencies (0.55 to 0.77) in Eastern Mediterranean Sea bass populations, which show considerably higher levels of resistance to VNN, as compared to susceptible West Mediterranean and Atlantic populations (0.15–0.25). Conclusions The SNP variant CHR3:10,077,301, through modulation of IFI27L2 and IFI27L2A genes, is likely the causative mutation underlying resistance to VNN in European sea bass. This is one of the first causative mutations discovered for disease resistance traits in fish and paves the way for marker-assisted selection as well as biotechnological approaches to enhance resistance to VNN in European sea bass and other susceptible species.